A Stakeholder Needs Assessment to Gauge the Interest in and Demand for a Child and Youth Care Postgraduate Specialization Certificate Program - Bellefeuille, Gerard (Advances in Social Sciences Research Journal, 2017)
Abstract The purpose of this needs assessment was to explore child and youth care (CYC) learning needs and interest of stakeholders in the development of a CYC postgraduate specialization certificate. A purposive sample strategy was used to recruit CYC practitioners and senior CYC administrators. The data collection strategy consisted of an online survey, an online discussion forum, a key-informant focus group, and a round-table discussion. Findings indicated that participants had a strong interest in a variety of professional development topics, including advanced mental health practice/expressive therapies, addictions, child protection, and family work.